2017
DOI: 10.1167/iovs.16-21270
|View full text |Cite
|
Sign up to set email alerts
|

The Charles Bonnet Syndrome in Patients With Neovascular Age-Related Macular Degeneration: Association With Proton Pump Inhibitors

Abstract: PURPOSE. We investigate the prevalence of the Charles Bonnet syndrome (CBS) in patients with neovascular age-related macular degeneration (AMD) and analyze the role of oral proton pump inhibitors (PPIs) and other potential risk factors. METHODS. A total of 510 consecutive patients with neovascular-AMD followed at a single tertiary center in Portugal were screened for CBS. Using a structured questionnaire, psychiatrically healthy individuals were interviewed systematically and divided into a CBS group and a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…(), Hou & Zhang (), Singh & Sørensen (), and Leandro et al. () all reported on patients with neovascular AMD consecutively seen in a clinical context, which may be more representative of the population seen in clinical practice. In these patients, the presence of CBS was associated with older age, worse BCVA, and intake of proton pump inhibitors (Leandro et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(), Hou & Zhang (), Singh & Sørensen (), and Leandro et al. () all reported on patients with neovascular AMD consecutively seen in a clinical context, which may be more representative of the population seen in clinical practice. In these patients, the presence of CBS was associated with older age, worse BCVA, and intake of proton pump inhibitors (Leandro et al.…”
Section: Resultsmentioning
confidence: 99%
“…In these patients, the presence of CBS was associated with older age, worse BCVA, and intake of proton pump inhibitors (Leandro et al. ). Singh & Sørensen () also found that patients who experienced CBS were more likely to be female and have lower BCVA in best‐seeing eye.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other risk factors that have been identified include age, social isolation, sensorial deprivation (including hear loss), low level of education, cerebrovascular disease, fatigue, and stress [5-7]. We have recently reported some of the related risk factors for CBS in a population of neovascular AMD patients [8]. Besides the influence of older age and visual impairment, proton pump inhibitor (PPI) intake was associated with a 2 times greater risk of developing the syndrome and should be recognized as a possible modifiable factor for CBS.…”
Section: Introductionmentioning
confidence: 99%